Thermal Distortion Analysis of Inflatable Antenna Structures Considering Inflation Gas - Xu,Yan (2016)
ABSTRACT This paper addresses the static distortion and stress analysis of inflatable antenna structures subjected to a thermal load, which is a very important type of load experienced by such structures during service in orbit. Non-linear finite element analysis methods for inflatable structures were formulized, and the thermal stress of thin films was considered. The dynamic relaxation method was used to address the singularity problem of the stiffness matrix for the non-pre-stressed membrane structures. When the thermal load is changing, the state of the inflation gas inside the structure chamber varies, as well as the thermal stress of the membrane material. An iterative algorithm was presented to solve this coupling problem between thermal load, the structures, and inflation gas. The presented algorithm has been implemented into an own finite element code of inflatable structures. The thermal deformation and the stress distribution of a 3.2-m inflatable antenna structure were analyzed to illustrate the feasibility of the numerical method. The results indicated that the change in the state of the inflation gas adversely affects the structural performance, so the inflation gas must be considered.